The Influence of Organizational Culture in Application of Information Technology Governance - Lanto Ningrayati Amali; Lillyan Hadjaratie; Sitti Suhada (Universitas Airlangga, 2018)
In this era of globalization, an organization needs to adapt to the competitions in order to maintain its existence. However, information technology (IT) governance development and application is sometimes not effective, which consequently ends as a failure. Such extent is attributable to lack of thorough analysis of organizational needs, particularly, in the scope of organizational culture. In this regards, this study attempts to carry out the contributions of organizational culture aspect to the development of IT governance. Good strategies of IT governance are ordinarily well applied in most organizations. The organizations, in fact, struggle to find a proper framework or model of IT governance with their characters. A quantitative method through document study and questionnaire. The data were obtained through The Organizational Culture Assessment Instrument (OCAI) questionnaire with 450 respondents. The importance of organizational culture towards the application of IT governance that an organization can decide a suitable model of development with the organization goals. The role of organizational culture is crucial for the leader, as one key factor of success in IT governance, in formulating harmonious strategies of IT utilization policy with business strategy. Furthermore, it also acts as a recommendation for organizations to design better IT governance which is suitable for organization strategies and vision.